FÓRUM DE DISCUSSÃO: PROFESSORES EM DIÁLOGO - Barreto, Talita de Assis (Intercâmbio, 2010)
This project is based on the dialogic approach to language (Bakhtin, 1992) and in ergologic approach (Schwartz, 1997). I present a methodological device used in researches about the presentation of projects in academic events as a teacher activity. A forum of discussion was done - a dialectual research procedure - aiming at the construction of meaning by subjects.